2020
DOI: 10.3390/genes11060709
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Involvement of Alternative Polyadenylation in Single-Nucleus Neurons

Abstract: Cleavage and polyadenylation are essential processes that can impact many aspects of mRNA fate. Most eukaryotic genes have alternative polyadenylation (APA) events. While the heterogeneity of mRNA polyadenylation isoform choice has been studied in specific tissues, less attention has been paid to the neuronal heterogeneity of APA selection at single-nucleus resolution. APA is highly controlled during development and neuronal activation, however, to what extent APA events vary in a specific neuronal cell popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…Notably, genes with long 3′‐UTRs show enrichment in neuronal functions. In accordance with what was observed in different brain cell types and tissues (Braz et al, 2017), both excitatory neurons and inhibitory neurons show differential usage of PASs for the same genes, showing that APA regulation is a cell‐type‐ and context‐specific mechanism (Wang et al, 2020). In a global analysis of APA during mouse retinal development, lengthening of the 3′‐UTR and increased usage of intronic PASs was also detected, suggesting a role for APA in the regulation of retinal development and maturation (Hu et al, 2017).…”
Section: Alternative 3′‐utr Rna Signatures In Cell States and Diseasesupporting
confidence: 83%
See 1 more Smart Citation
“…Notably, genes with long 3′‐UTRs show enrichment in neuronal functions. In accordance with what was observed in different brain cell types and tissues (Braz et al, 2017), both excitatory neurons and inhibitory neurons show differential usage of PASs for the same genes, showing that APA regulation is a cell‐type‐ and context‐specific mechanism (Wang et al, 2020). In a global analysis of APA during mouse retinal development, lengthening of the 3′‐UTR and increased usage of intronic PASs was also detected, suggesting a role for APA in the regulation of retinal development and maturation (Hu et al, 2017).…”
Section: Alternative 3′‐utr Rna Signatures In Cell States and Diseasesupporting
confidence: 83%
“…In mouse and human neural tissues, distal PASs are also preferentially selected, producing long 3′‐UTRs (Miura et al, 2013). As in Drosophila , the 3′‐UTR extensions had numerous conserved miRNA target sites that were enriched for known neural miRNAs, suggesting that posttranscriptional regulation of longer 3′‐UTRs by miRNAs and RBPs has a particular influence in the nervous system (Miura et al, 2013; Wang et al, 2020). Notably, genes with long 3′‐UTRs show enrichment in neuronal functions.…”
Section: Alternative 3′‐utr Rna Signatures In Cell States and Diseasementioning
confidence: 99%
“…In summary, eight model genes were used in the gene set for this analysis, and it was found that they were regulated by multiple transcription factors and other common mechanisms [37][38][39]. Transcription factor NFAT5 was the main regulator of gene concentration, and there was statistical significance in the difference of survival prognosis and immune cell infiltration in LUAD (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%